2019
DOI: 10.3390/ijerph16214281
|View full text |Cite
|
Sign up to set email alerts
|

Green Exercise: How Are Characteristics of Urban Green Spaces Associated with Adolescents’ Physical Activity and Health?

Abstract: This study investigates associations between characteristics of urban green spaces (UGSs) and adolescents’ self-reported green exercise (GE), general health, and body mass index (BMI). Data were collected through face-to-face personal interviews with 384 adolescents ages 13–19 between 1 March and 31 May, 2018 in UGSs in Aydın, Turkey. Multivariate regression analyses were conducted to examine associations controlling for confounding factors. Stratified analyses were also conducted to determine differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 69 publications
0
18
0
1
Order By: Relevance
“…Finally, both Gardsjord et al [ 32 ] and Moore et al [ 9 ] have addressed gender differences regarding urban space and physical activity: some studies have found girls to be less active than boys, partly due to perceived gender stereotypes (e.g., football is for boys). In contrast, Akpinar [ 42 ] found a positive correlation between the existence of sports fields and physical activity amongst girls.…”
Section: Consequences For Urban Green Space Designmentioning
confidence: 93%
See 1 more Smart Citation
“…Finally, both Gardsjord et al [ 32 ] and Moore et al [ 9 ] have addressed gender differences regarding urban space and physical activity: some studies have found girls to be less active than boys, partly due to perceived gender stereotypes (e.g., football is for boys). In contrast, Akpinar [ 42 ] found a positive correlation between the existence of sports fields and physical activity amongst girls.…”
Section: Consequences For Urban Green Space Designmentioning
confidence: 93%
“…Indeed, Gardsfjord et al [ 32 ] note that it is worth applying these ideas in UGS design; for young people, access to green space is critically important for promoting physical activity. Other studies have also demonstrated that children and young people prefer “naturalness”, whether in the form of trees or flowerbeds [ 40 , 42 ].…”
Section: Consequences For Urban Green Space Designmentioning
confidence: 99%
“…A growing number of studies suggest that exposure to natural outdoor environments can help improve human health and wellbeing by reducing stress, encouraging social relationships, and increasing physical activity [ 1 , 2 , 3 , 4 ]. The majority of these studies have focused on the benefits of doing outdoor activities in green spaces [ 5 , 6 ], indicating that this improves mental wellbeing and cognitive functioning [ 7 , 8 ]. Several studies also link living close to a green space with better overall mental health, reduced mental distress, lower rates of anxiety, and increased life satisfaction [ 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Concept analysis requires the identification of antecedents and consequences 9 . Availability of green spaces, neighborhood safety, walkability to community centers, and accessibility of community and health resources are some identified antecedents of EE 38–40 . As such, the antecedent of greater accessibility, neighborhood walkability, and green spaces increases physical activity among children 38 and older adults 39 .…”
Section: The Antecedents Of Environmental Enrichmentmentioning
confidence: 99%